The next Africa : an emerging continent becomes a global powerhouse - Bright, Jake.; Hruby, Aubrey (New York : Thomas Dunne Books/St. Martin's Press, 2015)
"After decades of resting on the world's economic margins, Africa is in the midst of tectonic transformation, redefining itself as a source of innovation and a destination for capital investment"--
"The Next Africa will change the way people think about the continent. The old narrative of an Africa disconnected from the global economy, depicted by conflict or corruption, and heavily dependent on outside donors is fading. A wave of transformation driven by business, modernization, and a new cadre of remarkably talented Africans is thrusting the continent from the world's margins to the global mainstream. Finally, The Next Africa suggests a fresh framework for global citizens, public policy-makers, and CEOs to approach Africa. It will no longer be "The Hopeless Continent", nor will it become an overnight utopia. Bright and Hruby offer a more nuanced, net-sum, and data-rich approach to analyzing an increasingly complex continent, reconciling its continued challenges with rapid progress. The Next Africa describes a future of a more globally-connected Africa where its leaders and citizens wield significant economic, cultural, and political power--a future in which Americans will be more likely to own African stocks, work for companies doing business in Africa, buy African hits from iTunes, see Nigerian actors win Oscars, and learn new African names connected to tech moguls and billionaires"--
Includes index.
Keywords: Economic development -- Africa; BUSINESS & ECONOMICS / International / Economics; BUSINESS & ECONOMICS / Knowledge Capital; Africa -- Foreign economic relations; Africa -- Foreign relations; Africa -- Economic conditions -- 21st century